2015
DOI: 10.3389/frym.2015.00015
|View full text |Cite
|
Sign up to set email alerts
|

Getting Lost in a Book: The Science of Reading Comprehension

Abstract: Have you ever felt like you got to know a character in a story, or felt like you could imagine the world she lived in? Have you ever wondered why the books we read seem to come to life in our minds? Studies from laboratories around the world are beginning to unravel this mystery. These studies show that when we read stories, our minds actually act like they are participating in the events in the story. This can make us feel like we can see what the characters see and feel what the characters feel. These findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…When asked to retell the story, children often changed the incongruent verb with the congruent one, indicating that they were monitoring the story from the character point of view . Consistently, Nyhout (2015) found that at the age of 7 children track characters' goals when listening to short narratives. Extending these observations to written texts, Dore et al (2018) proposed that ToM is also crucial for understanding written narratives, thus contributing to the development of reading comprehension.…”
Section: Discussionmentioning
confidence: 67%
“…When asked to retell the story, children often changed the incongruent verb with the congruent one, indicating that they were monitoring the story from the character point of view . Consistently, Nyhout (2015) found that at the age of 7 children track characters' goals when listening to short narratives. Extending these observations to written texts, Dore et al (2018) proposed that ToM is also crucial for understanding written narratives, thus contributing to the development of reading comprehension.…”
Section: Discussionmentioning
confidence: 67%
“…Y en el proceso narrativo se esperaría para esta edad un seguimiento más avanzado de los estados mentales y emocionales de los personajes, por ejemplo, el seguimiento de metas del personaje. Nyhout (2015) encontró en niños de 7 años una representación espontánea sobre la meta de los personajes; mediante el paradigma de tiempo de procesamiento, notó que los tiempos de respuesta de los niños eran más largos cuando las oraciones eran inconsistentes con la meta presentada al inicio de la narración (presentación en modalidad oral), respecto a las oraciones que eran consistentes.…”
Section: Discussionunclassified